Implementation of Management Economics in MSMEs in the Digital Era - Ambalao , Shapely; Sahetapy, Kenneth (Fakultas Ekonomi & Bisnis Universitas Muslim Indonesia, 2025)
Digital MSMEs in Indonesia are facing new dynamics amid rapid technological transformation. This study aims to evaluate the extent to which managerial economic principles have been applied in the management of digital-based MSMEs. Using a Systematic Rapid Review approach to analyze five academic articles published in 2024, the study finds that managerial capability and e-commerce utilization are dominant factors in improving efficiency and competitiveness. The findings also reveal significant challenges such as low managerial and digital literacy, and suboptimal policy support. Therefore, a sustainable strategy emphasizing managerial training, data utilization, and cross-sector collaboration is needed to enhance MSME performance in the digital era.